Precise Dimensional Measurement of A Helicopter model using Geodetic and Non-Contact Measurement Techniques - M. Idris, Khairulnizam; Setan, Halim (2008)
Industrial measurement requires high precision instrumentation for a good data gathering and analysis. Nowadays, we have offered too much instrumentation from conventional such as robotic total station and non-contact measurement like digital photogrametry and laser scanning. LEICA TCA2003 robotic total station and TM5100 electronic theodolite is a high precision instrument for the highest requirements in industrial/deformation surveying with the angle and distance measuring accuracies of 0.5â€? and 1mm respectively. This paper focuses on the industrial observation campaign using geodetic technique and non-contact technique. Non-contact technique refers to photogrametry and laser scanning. This project is collaboration between Surveying Engineering Research Group Laboratory and Aeronautic Laboratory, Universiti Teknologi Malaysia. The observation object is Eurocopter 350Z Prototype Helicopter Model helicopter.